2008
DOI: 10.1075/eurosla.8.06mul
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual first language acquisition at the interface between syntax and pragmatics

Abstract: The present article provides an overview of some recent research in bilingual first language acquisition with special reference to Romance languages. It addresses two language contact phenomena, language mixing at the lexical level and crosslinguistic influence at the syntactic level. For both contact phenomena, there is evidence that they are unrelated to language dominance (as measured in terms of MLU). Language mixing is negatively correlated with the number of utterances per minute, a measure for language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…vowel production (Bullock and Gerfen, 2004), voice onset time (Kehoe et al, 2004;Zampini and Green, 2001), and intonation (Colantoni and Gurlekian, 2004); and syntax and syntax-related interfaces, e.g. verb placement (Döpke, 1998), adjective-noun order (Nicoladis, 2003), tense and aspect (Sanchez, 2004), and argument omission (Montrul, 2004;Müller, 2007;Müller and Hulk, 2001;Serratrice et al, 2004;Toribio, 2004;Yip and Matthews, 2000).…”
Section: Multicompetence and Variation In Native Language Productionmentioning
confidence: 99%
“…vowel production (Bullock and Gerfen, 2004), voice onset time (Kehoe et al, 2004;Zampini and Green, 2001), and intonation (Colantoni and Gurlekian, 2004); and syntax and syntax-related interfaces, e.g. verb placement (Döpke, 1998), adjective-noun order (Nicoladis, 2003), tense and aspect (Sanchez, 2004), and argument omission (Montrul, 2004;Müller, 2007;Müller and Hulk, 2001;Serratrice et al, 2004;Toribio, 2004;Yip and Matthews, 2000).…”
Section: Multicompetence and Variation In Native Language Productionmentioning
confidence: 99%
“…For the object domain, it has already been shown that there is a strong correlation between language fluency and the amount of object omission (cf. Müller (2008) and Hauser-Grüdl and Arencibia Guerra (2007)). The more fluent the child is/becomes in this language, the less object omissions are observed.…”
Section: Discussionmentioning
confidence: 95%
“…The nature of the data, spontaneous production data, makes it impossible to disentangle a representational and a processing approach. However, as pointed out by Müller (2008), if a processing approach is to be favored, we would expect external factors to influence the direction of the influence. More specifically, we would expect that a child with German as a weak language shows signs of cross-linguistic influence of the Romance language when using subjects and objects respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature in simultaneous bilingual acquisition has argued that children exposed to two different languages develop separate linguistic systems. However, the potential of one linguistic system affecting the other as a form of cross-linguistic influence has been the focus of considerable research (Genske, 2014;Kang, 2013;Kupisch, 2007;Matthews, Cheung and Yip, 2017;Müller, 2008;Serratrice, Sorace and Paoli, 2004;Yip and Matthews, 2007). There has been continuing debate concerning the domains in which cross-linguistic influence may occur and the possible sources of its occurrence.…”
Section: Background/previous Researchmentioning
confidence: 99%